Cervical cancer screening uptake and determinant factors among women in Ambo town, Western Oromia, Ethiopia: Community‐based cross‐sectional study - Shewaye F. Natae (Wiley, 2021)
Abstract Background Cervical cancer is the second most common cancer and the leading cause of cancer‐related death in Ethiopian women. About 77.6% of women died of 6294 new cases reported in 2019. Early screening for cervical cancer has substantially reduced morbidity and mortality attributed to it. In Ethiopia, most of the women visit the health facilities at the late stage of the disease in which the offered intervention is not promising. Therefore, we aimed to assess the level of cervical cancer screening uptake and its determinant among women of Ambo town, Ethiopia. Methods Community‐based cross‐sectional study was conducted among 422 women aged 20–65 years. An interviewer‐administered questionnaire was used to collect the data. Data were analyzed using SPSS version 25. Estimates were presented using an odds ratio (OR) with 95% CI. Statistical significance was declared at a p value of <0.05. Results In the present study, 392 women were participated giving a response rate of 93%. Only 8.7% (34) of the study participants were received cervical cancer screening in their lifetime. Being in the age group of 30–39 years (AOR = 3.2, 95% CI: 1.22, 8.36), having cervical cancer‐related discussions with a healthcare provider (AOR = 3.5; 95% CI: 1.17, 10.7), and knowing the availability of cervical cancer screening service (AOR = 2.8; 95% CI: 1.03, 7.87) were significantly associated with uptake of cervical cancer screening. Conclusion In this study, cervical cancer screening uptake is very low. Our study identifies clues for determinants of cervical cancer screening uptake. Thus, further studies using a better study design might be helpful to explore determinants of low utilization of CC screening services and suggest an appropriate intervention that increases CC screening uptake in the study area.